POSTPARTUM UTERINE PROLAPSE IN A SOW-A CASE REPORT - B. Chandra Prasad; Manda Srinivas (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A sow aged 3 years was presented to veterinary clinical complex, Gannavaram for treatment of prolapsed uterus. On examination averted uterine horns were found hanging from vulva and tear was observed in the vaginal wall. The prolapsed uterine mass was congested and oedematous. The averted mass was cleaned thoroughly and attempted for reposition but failed. The sow lost its life after 30 hours.